A Microhistory of British Antislavery Petitioning. Issue 3 (2019) - Huzzey, Richard
Abstract : This article refines our understanding of abolitionism as "the first modern social movement" through a microhistory of abolitionism in an eighteenth- and nineteenth-century British town. Examining requisitions, which collected signatures calling on a mayor to convene public meetings to launch parliamentary petitions or other associational activities, the article shows how antislavery mobilization in Plymouth grew amongst a multiplying variety of religious, political, cultural, and economic institutions. Through a prosopography of those initiating antislavery petitions, an analysis of the other requisitions they supported, and qualitative evidence from leading abolitionists' personal papers, the article details the ways local leaders raised petitions for a national campaign. Civic and religious dynamism at this local level facilitated new forms of contentious mobilization on national and imperial issues. The article therefore directs causal attention to those socioeconomic changes that underpinned the associational cultures of abolitionism.